Blue book of coastal vessels Thailand = Samutphāp rư̄a chāifangthalē khō̜ng Prathēt Thai poksīnamngœ̄n (White Lotus Press, 2000)
Blue book of coastal vessels Thailand is an exhaustive study of the wooden-hulled fishing boats in the Gulf of Thailand and in the Andaman Sea. It was originally designed as an identification aid for military personnel to locate suspicious boats during the Vietnam War period. But this book is much wider in scope. It provides a wealth of information to researchers in marine studies: boat types, technical data, fish species available in the gulf, etc. Many things may have changed with the decline of fish stocks due to over-fishing, destruction of mangroves, or pollution. The first part of the book gives the history and religious influences on boat operations, fishing areas and techniques. The second part describes the classes and types of wooden-hulled coastal vessels. This book is an indispensable tool for anyone who wants to make comparative studies of the coastal fishing industry or boat building in the region.